2021
DOI: 10.3390/ijms22073598
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-Donors Can Induce Apoptosis and Attenuate Both the Akt and the Erk1/2 Mediated Proliferation Pathways in Breast and Lung Cancer Cell Lines

Abstract: Dietary methyl-donors play important roles in physiological processes catalyzed by B vitamins as coenzymes, and are used for complementary support in oncotherapy. Our hypothesis was that methyl-donors can not only assist in tolerating cancer treatment but may also directly interfere with tumor growth and proliferation. Therefore, we investigated the proposed cancer inhibitory effects of methyl-donors (in a mixture of L-methionine, choline chloride, folic acid, and vitamin B12) on MCF7 and T47D breast cancer as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Previously, we described that methyl donors are able to induce apoptosis and attenuate proliferation pathways in breast and lung cancer cell lines [ 33 ]. In our present study, we aimed to explore if similar changes could be detectable in Panc-1 cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we described that methyl donors are able to induce apoptosis and attenuate proliferation pathways in breast and lung cancer cell lines [ 33 ]. In our present study, we aimed to explore if similar changes could be detectable in Panc-1 cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found significantly increased subG1 fraction in cell cycle analysis, which indicates apoptotic cells; therefore, we investigated the intrinsic apoptotic pathway based on our previous study [ 33 ]. We found significantly increased pro-apoptotic Bak, Puma and Caspase-9 protein levels after methyl-donor treatment, but not in the case of the cleaved Caspase-3 level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is an expectation and necessity to measure and evaluate the effects of these vitamins, compounds and products [6,7,10,38]. Several studies suggested that dietary methyl-donors and related vitamins can contribute to cancer prevention [8,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake of methyl donors (such as folate, choline, betaine, methionine and vitamin B2, B6 and B12) could have important role in cancer prevention by reducing the risk of cancer and could contribute to the success of cancer therapies and to reach better quality of life (QoL) of the patients [6][7][8]. Dietary methyl donors are food components, which provide methyl groups for the one-carbon metabolism, which consists of two main metabolic cycles: the folate cycle and the methionine cycle [9].…”
Section: Introductionmentioning
confidence: 99%